'Our work was in the service of the suffering of mankind': a case study of the motives of the Easternfront Ambulance nurses, 1941–1944. Issue 2 (3rd April 2019) - van der Veen, Sietske
ABSTRACT: During World War Two, a group of Dutch nurses chose to join the Nederlandse Ambulance ('Easternfront Ambulance'), a controversial though currently relatively unknown field hospital for the eastern front. In doing so, they supported the German war effort. This case study elaborates on the motives of these women to make a choice that was ultimately determined as 'wrong', by emphasising their unique gender role of nurse in the public sphere. By providing an insight into a relatively small group of 'wrong' women, this article aims to act as a call for further research into the gender context of limitations and opportunities of Dutch women during the German occupation. These nurses appear to have had various intentional and unintentional motives for enlisting. Nearly all of them later claimed they had pursued a 'calling'. They had all been Nazi or Nationalist Socialist Movement in the Netherlands sympathisers and they had all enjoyed material benefits due to their position with the field hospital. In a few cases, it seems they had longed for interaction with soldiers, or men in general, and sometimes they had simply craved for an adventurous life far from home.